Electronic Tuning of Iron–Oxo‐Mediated CH Activation: Effect of Electron‐Donating Ligand on Selectivity. Issue 43 (11th September 2013) - Hitomi, Yutaka; Arakawa, Kengo; Kodera, Masahito
Abstract We have reported previously that an iron(III) complex supported by an anionic pentadentate monoamido ligand, dpaqH (dpaqH=2‐[bis(pyridin‐2‐ylmethyl)]amino‐N‐quinolin‐8‐yl‐acetamido), promotes selective CH hydroxylation with H2O2 with high regioselectivity. Herein, we report on the preparation of FeIII–dpaq derivatives that have a series of substituent groups at the 5‐position of a quinoline moiety in the parent ligand dpaqH (dpaqR, R: OMe, H, Cl, and NO2), and examine them with respect to their catalytic activity in CH hydroxylation with H2O2. As the substituent group becomes more electron‐withdrawing, both the selectivity and the turnover number increase, but the selectivity of epoxidation shows the opposite trend.